If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-6a + -6) = 0 Reorder the terms: -8(-6 + -6a) = 0 (-6 * -8 + -6a * -8) = 0 (48 + 48a) = 0 Solving 48 + 48a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 48a = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 48a = 0 + -48 48a = 0 + -48 Combine like terms: 0 + -48 = -48 48a = -48 Divide each side by '48'. a = -1 Simplifying a = -1
| 110=-4-5 | | pw+20s=x | | 7g+14-5g=18 | | 12x^6+324x^2-16x^9=0 | | -58.109=v+-47.736 | | -4-m=-41 | | 11x-7+3x-1+50=180 | | 22x-7-12x+2=20x-7-10x+17 | | -14-(-5)= | | 1-m+7-6+10m= | | 4m=-17 | | -81-9x=139+x | | 2x-3y+21=0 | | 5x+14=-17 | | -8x+5=28 | | X=100(.2x) | | 11j+4= | | -11(y+3)+5(3y-6)=3(y-3)+13 | | 11x+4-5x=21+7x-3 | | A(x)=x+6x+13 | | 3+21x+14x+12+40=180 | | -2(x-3)=-4x+20 | | X=100+(.2*x) | | lnx+4=1 | | 12x+6-(3x-5)=79 | | -6x=798 | | 32-17+2z=13 | | 8=-1+x | | 3x+11=4X-21 | | 4x+x-5=20 | | 2(x+1)1-4=12 | | 100=x(.02) |